2022
DOI: 10.1007/s10900-022-01121-4
|View full text |Cite
|
Sign up to set email alerts
|

A Review of You Tube Content to Assess US Mental Health During the Covid-19 Pandemic

Abstract: Mental health concerns have increased in prevalence since the beginning of the COVID-19 pandemic. Many turn to online resources for relevant information. The purpose of this study is to describe the availability of mental health information on YouTube, and to assess the relevance of the videos’ content in relation to the actual need of the population. The 100 most-watched YouTube videos in English resulting from a YouTube search of “COVID-19” and “mental health” were evaluated. Of mental health conditions, anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…Our Google Trends analysis also found an increased public interest in mindfulness contents via YouTube since the middle of 2010. Some studies found a critical link between mental health and YouTube content during the COVID-19 pandemic [53,54]. Nevertheless, according to our bibliographic analysis, studies in this field do not seem to consider online platforms such as YouTube as an important research topic in the context of mindfulness research.…”
Section: Implications On the Public And Research Fieldsmentioning
confidence: 77%
“…Our Google Trends analysis also found an increased public interest in mindfulness contents via YouTube since the middle of 2010. Some studies found a critical link between mental health and YouTube content during the COVID-19 pandemic [53,54]. Nevertheless, according to our bibliographic analysis, studies in this field do not seem to consider online platforms such as YouTube as an important research topic in the context of mindfulness research.…”
Section: Implications On the Public And Research Fieldsmentioning
confidence: 77%
“…For example, higher levels of loneliness were reported to be associated with YouTube use [63,71] and vice versa [75]. However, there are concerns about YouTube's recommendation algorithms, which could better present safe and accurate information on suicide [66,70,72,73,83]. It may be perceived that previous systematic reviews weaken the potential originality of the current study.…”
Section: Findings Of Current Studymentioning
confidence: 82%